Pengajaran Puisi dengan Metode Discovery-Inquiry - Yuli Tiarina (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2009)
The goal of teaching literature is enabling students to enjoy, comprehend, explore and use literary work for improving their knowledge and language skill as well. Besides that, it is also aimed at encouraging students to master and dig the distinctive points of literary work genres, namely prose, drama and poem. In fact, teaching literature, especially teaching poem for elementary students is not an easy job. Because it becomes a problem sometime for an English teacher to make their students love and enjoy poem. So that, an appropriate teaching method is needed to solve that problem, even there is no best method which can meet all of teaching and learning goals. One of recent method that is widely used by English teacher recently is Contextual Teaching Learning (CTL). The principles of CTL have high possibilities to be applied, they are; contructing, modelling, discovery, learning community and questioning. Dealing with Discovery-Inquiry method, Carin in mentioned that Discovery-Inquiry is a teaching method that give great chances for students to get involved and using their mental process to dig and make the discoveries  for materials that they are studied. This method designs the situation that empowers students to activate their learning experience. Students may study outside of class for observation and getting inspiration, next time that experience can be written in a poem, so unconsciously they have learned how to write and explore a poem. Key words: puisi, inquiry-discovery, modeling, learning community